EU Banking Union: Lessons for non-eurozone Transition countries - Šoskic, Dejan (Industrija, 2015)
Eurozone has gone through turmoil of sovereign debt crisis just after the detrimental effect of global financial crises of 2007/2008. Sovereign debt crisis of the eurozone was caused by bank-sovereign interdependence and lack of fiscal union in the eurozone. Financial fragmentation in the eurozone financial markets was an immediate outcome. Banking union of the EU is a regulatory and institutional remedy for main financial problems of the eurozone post global financial crisis. It is clear signal that lessons have been learned from the two crisis. Stricter regulation (single rule book) aims to increase the quality of banks. Single Supervisory Mechanism (SRM), and Single Resolution Mechanism (SRM) aim to unify and better the standards of supervision and resolution in the EU. With emphasis on bail-ins, and EU level backstops, bank-sovereign interdependence should be dismantled and chances of financial crisis reoccurrence with huge costs for taxpayers should be significantly lower. There are important elements of Banking Union that could be introduced in non-eurozone transition countries both members and nonmembers of the EU.
Keywords: non-eurozone countries; Sovereign debt crises; EU-European; Banking Union